Genetic Characterization of Mutations Related to Conidiophore Stalk Length Development in Aspergillus niger Laboratory Strain N402 - Demirci, Ebru; Arentshorst, Mark; Yilmaz, Baran; Swinkels, Aram; Reid, Ian D.; Visser, Jaap; Tsang, Adrian; Ram, Arthur F. J. (Frontiers in Genetics, 2021)
Aspergillus niger is an important filamentous fungus in industrial biotechnology for the production of citric acid and enzymes. In the late 1980s, the A. niger N400/NRRL3 strain was selected for both fundamental and applied studies in relation to several processes including gluconic acid and protein production. To facilitate handling of A. niger, the N400 wild-type strain was UV mutagenized in two consecutive rounds to generate N401 and N402. N402 was used as a reference laboratory strain and exhibits a reduced conidiophore stalk length and radial growth phenotype. The conidiophore stalk length and radial growth of A. niger strain N400 was determined and compared to N401 and N402. The length of N400 conidiophore stalks (2.52 ± 0.40 mm) was reduced in N401 and N402 to 0.66 ± 0.14 mm and 0.34 ± 0.06 mm, respectively. Whereas N400 reached a colony diameter of 6.7 ± 0.2 cm after 7 days, N401 and N402 displayed reduced radial growth phenotype (4.3 ± 0.1 and 4.1 ± 0.1, respectively). To identify the mutations (dubbed cspA and cspB) responsible for the phenotypes of N401 and N402, the genomes were sequenced and compared to the N400 genome sequence. A parasexual cross was performed between N400 and N402 derivatives to isolate segregants which allowed cosegregation analysis of SNPs and indels among the segregants. The shorter conidiophore stalk and reduced radial growth in N401 (cspA) was found to be caused by a 9-kb deletion on chromosome III and was further narrowed down to a truncation of NRRL3_03857 which encodes a kinesin-like protein homologous to the A. nidulans UncA protein. The mutation responsible for the further shortening of conidiophore stalks in N402 (cspB) was found to be caused by a missense mutation on chromosome V in a hitherto unstudied C2H2 transcription factor encoded by the gene NRRL3_06646. The importance of these two genes in relation to conidiophore stalk length and radial growth was confirmed by single and double gene deletion studies. The mutations in the laboratory strain N402 should be taken in consideration when studying phenotypes in the N402 background.